KOMUNIKASI INTERPERSONAL GURU DI SMK NEGERI 1 ANGKOLA TIMUR - HARAHAP, FITRIANI (Institut Pendidikan Tapanuli Selatan, 2017)
This study aimed to determine the interpersonal communication of the teachers at State Vocational School of Angkola Timur.The teachers at State Vocational School of Angkola Timur, South Tapanuli become the respondents to interviewed. Interview, observation and documentation are the tools used for this research.The results showed that good interpersonal communication can improve the productivity and organizational citizenship behavior (OCB) of teachers. In this case, the existence of good interpersonal communication among teachers will increase the productivity and organizational citizenship behavior (OCB) of teachers to their work. Teachers arouse volunteerism to help co-workers despite their work duties, maintain good relationships with fellow workers, and accept any policies and procedures established by the organization, this is proving to have an impact on their organizational citizenship behavior (OCB). Teachers have extra behavior toward their organizations because teachers are dedicated to completing their tasks prematurely, reporting to superiors or co-workers first when not in work, and increasing teachers sense of responsibility to comply with school rules and regulations even in the absence of a person who are watching, care about the development and changes that occur in the organization and participate in various activities organized by the school.